2020
DOI: 10.1002/agg2.20043
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term spatiotemporal relationship between plant and soil properties on natural turfgrass sports fields

Abstract: The present study was conducted to explore the spatiotemporal relationship between several plant and soil properties on two natural turfgrass sports fields comprised of native and sand-capped soils before and after irrigation. Minimal differences in strength of relationship and spatical variability among field properties occurred from before to after irrigation at both fields. A number of significant relationships between field properties were observed overall, although significance did not always result in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Straw et al. (2020) studied spatial variability of bermudagrass grown on two soil types within American football fields. The authors found correlation coefficients of 0.57 and 0.62 before and after irrigation, respectively, on the sandy loam field, and 0.41 and 0.24 before and after irrigation, respectively, on the sand capped field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Straw et al. (2020) studied spatial variability of bermudagrass grown on two soil types within American football fields. The authors found correlation coefficients of 0.57 and 0.62 before and after irrigation, respectively, on the sandy loam field, and 0.41 and 0.24 before and after irrigation, respectively, on the sand capped field.…”
Section: Resultsmentioning
confidence: 99%
“…Hong, Bremer, and Van der Merwe (2019b) found VWC to be positively correlated (r = 0.59) with NDVI measured using an active handheld sensor on creeping bentgrass plots in a controlled study. Straw et al (2020) studied spatial variability of bermudagrass grown on two soil types within American football fields. The authors found correlation coefficients of 0.57 and 0.62 before and after irrigation, respectively, on the sandy loam field, and 0.41 and 0.24 before and after irrigation, respectively, on the sand capped field.…”
Section: Correlation Of Vwc and Proximal Ndvimentioning
confidence: 99%
“…The highest dose of sewage sludge (1,428 g m -2 ) positively influenced the Normalized Difference Vegetation Index (NDVI), with an average of 0.53 (Figure 2A), 39.41% higher compared to control treatment (0 g m -2 ). This index can indicate when the lawn is exposed to stresses such as trampling/compaction, utilization, and water deficit (Kerr et al, 2019;Straw et al, 2020). NDVI can be used as an alternative to evaluate the DCGI in the turfgrass (Caturegli et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The patterns of variation in the Temple field (Figure 7) do not seem to relate to patterns of variation in elevation (Figure 2c) which is not particularly surprising, given the unpredictable patterns of soil texture within this field. Straw et al [38] also found that the strength of relationships between soil moisture and grass health patterns can vary between fields and with different soil types. Given the elevation patterns of the field, the unexpected dry areas at the base of the slope (western side of the field Figure 7d,g) could be related to the combination of the soil texture and the management practice of applying 30% less water to the three rows of sprinklers at the base of the slope in the 2021 growing season.…”
Section: Temple Field-spatial and Temporal Patternsmentioning
confidence: 99%